Looking Beyond the Church Tax: Families and the Disaffiliation of Austrian Roman Catholics - Berghammer, Caroline (Journal for the scientific study of religion, 2017)
This study aims to understand the reasons why Roman Catholics leave the church based on the example of Austria, a country with high rates of disaffiliation since the 1980s. Although previous research focused mainly on the church tax, this study provides a more comprehensive analysis based on a mixed-methods approach that reveals the central relevance of the family in the process. We began by conducting and analyzing 19 qualitative interviews with former Catholics. Next we used the Generations and Gender Survey (two-wave representative panel data) to study the characteristics of Catholics who disaffiliated in the intersurvey period (2008-2012). Two types could be distinguished in the qualitative and the quantitative sample: attached and distant leavers. Both rarely attended religious services and were critical of the church, but attached leavers held a private form of religiosity and engaged in religious practices whereas distant leavers self-identified as agnostics or atheists. The church tax was the main reason for disaffiliation among attached leavers while distant leavers disaffiliated on ideological grounds. One identical factor, however, was of major importance for explaining church-leaving behavior among both types: family-related matters and experiences. We conclude that family members and family transitions play a major role in the process of religious disaffiliation.